(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The objective of this presentation is to explore into the assessment and its relationship with interculturality and inclusion in the classroom, through the review of 12 articles, which allow us to understand at the assessment process is a system that adapts different methods that to current needs. This document intends to establish evaluation as an inclusive and intercultural process, being essential the use of different methodologies and strategies, which give importance to the diverse population that may be present in the classroom, promoting a culture of recognition and appropriation for the construction of a modern society oriented to the principle of interculturality, basing the feedback as an important value in meaningful learning.